Status gingiva anak usia 14-15 tahun di daerah dataran tinggi dan di daerah pesisir pantai - Zarra, Jizel; Siagian, Krista V.; ., Juliatri (Universitas Sam Ratulangi, 2016)
Abstract: Gingiva is prone to any disturbances. Poor dental and oral health can cause inflammation of the gingiva. Children aged 14-15 years have already permanent teeth that had fully grown. This study was aimed to obtain the gingival status of children aged between 14-15 years old living in the highland and at the coastal area. This was a descriptive observational study with a cross sectional design. The study population was all students aged 14-15 years at SMP GMIM Rurukan and SMP PGRI Tandurusa (Junior high schools). Subjects were 30 students obtained by using purposive sampling. Data of gingival status were obtained from examination of gingival index according to Loe and Silness. The results showed that the gingival status of subjects living in the highland were mild inflammatory category (66.7%) and moderate inflammatory category (33.3%), whereas of those at the coastal area were mild inflammatory category (93.4%) and moderate inflammatory category (3.3%). Keywords: gingival status, children 14-15 years, highland, coastÂ Abstrak: Gingiva merupakan jaringan yang rentan terhadap berbagai gangguan. Buruknya kesehatan gigi dan mulut dapat menimbulkan peradangan gingiva. Pada kelompok usia 14-15 tahun anak telah memiliki gigi permanen yang sudah tumbuh lengkap dalam rongga mulut. Penelitian ini bertujuan untuk mengetahui status gingiva anak usia 14-15 tahun di daerah dataran tinggi dan di daerah pesisir pantai. Jenis penelitian ialah deskriptif observasional dengan desain potong lintang. Populasi penelitian ialah seluruh siswa berusia 14-15 tahun yang bersekolah di SMP GMIM Rurukan dan SMP PGRI Tandurusa. Subjek penelitian diambil sebanyak 30 siswa menggunakan purposive sampling. Pengumpulan data menggunakan formulir pemeriksaan status gingiva berdasarkan indeks gingiva Loe and Silness. Hasil penelitian mendapatkan status gingiva subjek di daerah dataran tinggi tergolong kategori inflamasi ringan (66,7%) dan kategori inflamasi sedang (33,3%), sedangkan status gingiva subjek di pesisir pantai tergolong kategori inflamasi ringan (93,4%) dan kategori inflamasi sedang (3,3%). Kata kunci: Status gingiva, usia 14-15 tahun, dataran tinggi, pesisir pantai